Literasi Digital: Strategi Pembelajaran IPAS di Kelas V SDN Bakaran Wetan 03 - Sulistiyowati, Sulistiyowati; Erik Aditia Ismaya (JANACITTA, 2024)
AbstractThis research is research using a mix method strategy to provide information about the implementation of digital literacy learning strategies for class V students at SDN Bakaran Wetan 03. The results of the research are, 1) the implementation of learning from all aspects went well. Through observations and documentation carried out by the teacher, information can be obtained that the preparation and implementation of the research is going well. Adequate supporting facilities and infrastructure are available, both those provided by the school and those brought by students independently. 2) the level of effectiveness of learning using digital literacy strategies can be said to be very effective. Through short interviews between teachers and students, it shows that students are comfortable in learning and obtaining the information they are looking for. Abstrak Penelitian ini merupakan penelitian dengan strategi mix methodes untuk memberikan informasi tentang pelaksanaan strategi pembelajaran literasi digital pada siswa kelas V SDN Bakaran Wetan 03. Hasil penelitiannya adalah, 1) pelaksanaan pembelajaran dari semua aspek berjalan dengan baik. Melalui pengamatan dan dokumentasi yang dilakukan oleh guru dapat diperoleh informasi bahwa persiapan maupun pelaksanaan penelitian berjalan dengan baik. Sarana dan prasarana pendukung tersedia secara memadai baik itu yang disediakan oleh sekolah maupun yang dibawa siswa secara mandiri.  2) tingkat keefektifan pembelajaran menggunakan strategi literasi digital dapat dikatakan sangat efektif. Melalui wawancara singkat antara guru dan siswa menunjukkan bahwa siswa nyaman dalam belajar dan memperoleh informasi yang mereka cari.